(untitled) (Wire Insights: Journal of Innovation Insights, 2026)
The article examines the economic essence and content of organizational competitiveness under modern market conditions. It highlights the role of competitiveness as a key factor of sustainable development in enterprises. The study explores structural elements, internal and external factors, competitive advantages, and strategic tools influencing competitiveness. Special attention is given to innovation, digital transformation, and consumer orientation as determining components of long-term market success. The paper emphasizes a systematic approach to competitiveness management as a basis for improving efficiency and investment attractiveness of organizations